AN ANALYSIS OF CODE SWITCHING USED BY EMILY COOPER IN THE SERIES EMILY IN PARIS SEASON 1 (2020) - Lamabelawa, Muharram Tuan Pati Naren; Nurhamidah, Idha (Jurnal Ilmiah Penelitian Mahasiswa, 2024)
This research analyzes the code-switching behavior of the character Emily Cooper in the series "Emily in Paris" Season 1 (2020). The focus is on identifying the types of code-switching she uses and the social factors influencing her code-switching decisions. The study employs Poplack's theory, as cited by Romaine, to categorize the types of code-switching. A descriptive qualitative method is utilized in this research. Data collection involved reading the series script, identifying instances of code-switching, classifying them, and reducing the data to relevant examples. Primary data were gathered from the series script, while secondary data were sourced from articles, journals, and previous studies related to the topic. Data analysis was conducted using a sociolinguistic approach. The analysis revealed that Emily Cooper uses three types of code-switching: intra-sentential, inter-sentential, and tag switching. The shift between English and French was analyzed according to Poplack's theory, citing Romaine. The factors influencing Emily's code-switching include the need to adapt to the French social environment, efforts to show appreciation for French culture and language, and strategies to gain trust and engagement in social interactions.Keywords: Code Switching, Emily Cooper, Emily In Paris season 1 (2020), Sociolinguistic approach, Poplack's theory